2015
DOI: 10.2174/1874922401507010086
|View full text |Cite
|
Sign up to set email alerts
|

The Macau Family-in-Transition: The Perceived Impact of Casino Employment on Family Relationships Among Dealer Families

Abstract: Although there is growing consideration of the negative impacts that are instigated by the booming gaming industry on the physical health and job satisfaction of casino employees in Macau, a critical research gap exists in the understanding of the perceived impacts of casino employment on the family life of the dealers. By drawing on evidence from a qualitative study carried out in Macau, the specifics of the changes in the family lives among dealer families and how family relationships have been affected by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Some academics have considered the phenomenon of ‘absent parents’ in Macau, where many parents have to work the night shift in casinos (Chan et al ., ; van Schalkwyk, Tran and Chang, ). When the children come home from school, their parents are getting ready for work or have already left for work.…”
Section: Unique Family Characteristics and Challengesmentioning
confidence: 98%
See 2 more Smart Citations
“…Some academics have considered the phenomenon of ‘absent parents’ in Macau, where many parents have to work the night shift in casinos (Chan et al ., ; van Schalkwyk, Tran and Chang, ). When the children come home from school, their parents are getting ready for work or have already left for work.…”
Section: Unique Family Characteristics and Challengesmentioning
confidence: 98%
“…They also work in shifts, which reduces time with their family. In balancing work commitments and family relationships, they may experience stress, which can also negatively affect their marital relationship (Chan, Kwok and Siu, ).…”
Section: Unique Family Characteristics and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al . () indicated that the families‐in‐transition phenomenon is now relevant to Macau, in that dealer families are undergoing changes due to the impact of casino employment. While financially positive, this has neither improved family bonding nor led to a large‐scale transformation of family relations with greater harmony and functionality.…”
Section: Working With Families‐in‐transition In Macaumentioning
confidence: 99%
“…In family therapy, working with impoverished families has been carried out against the implications of working with larger systems (Minuchin et al ., ). However, it is challenging for family therapists in Macau to negotiate with casino enterprises and the social system (Chan et al ., ) to address the poor sleep quality of dealers, particularly those with lower incomes. In addressing this problem, therapists should be sensitive not only to work‐family stress but also the linkage between financial burden and poor sleep quality, and thus consider socio‐economic background by establishing a platform that alleviates financial concerns.…”
Section: Gender and Class Sensitivity In Macaumentioning
confidence: 99%